An "almost-too-late" warning mechanism for currency crises - Jesús Crespo Cuaresma; Tomás Slacik (Bank of Finland, Institute for Economies in Transition (BOFIT), 2007)
We propose exploiting the term structure of relative interest rates to obtain estimates of changes in the timing of a currency crisis as perceived by market participants.Our indicator can be used to evaluate the relative probability of a crisis occurring in one week as compared to a crisis happening after one week but in less than a month.We give empirical evidence that the indicator performs well for two important currency crises in Eastern Europe: the crisis in the Czech Republic in 1997 and the Russian crisis in 1998.
URN:NBN:fi:bof-201408071896
Keywords: F31; F34; E43; 330; Currency crisis; term structure of interest rates; transition economies